CHILDHOOD OBESITY: CURRENT SITUATION (CIPEEX, 2025)
Introduction: The main part of human development occurs in childhood, therefore, increasing childhood obesity is a concern due to its high incidence. Objective: To identify the main current causes of the increase in childhood obesity. Methods: This research is a bibliographic study in which scientific articles were reviewed, articles that emphasized childhood obesity. Result: After the review, the data reveal that childhood obesity stems from several factors, such as poor diet, parental influence, and other factors. Conclusion: Childhood obesity is becoming an increasingly recurrent problem, from several sources, which is a concern for general health in the future. Therefore, creating ways to reverse this problem is urgent and necessary.
Keywords: Childhood obesity; Poor Diet; Technology; Children